FOXF2 is required for cochlear development in humans and mice. (17th December 2018) - Bademci, Guney; Abad, Clemer; Incesulu, Armagan; Elian, Fahed; Reyahi, Azadeh; Diaz-Horta, Oscar; Cengiz, Filiz B; Sineni, Claire J; Seyhan, Serhat; Atli, Emine Ikbal; Basmak, Hikmet; Demir, Selma; et al.
Abstract: Molecular mechanisms governing the development of the human cochlea remain largely unknown. Through genome sequencing, we identified a homozygous FOXF2 variant c.325A>T (p.I109F) in a child with profound sensorineural hearing loss (SNHL) associated with incomplete partition type I anomaly of the cochlea. This variant is not found in public databases or in over 1000 ethnicity-matched control individuals. I109 is a highly conserved residue in the forkhead box (Fox) domain of FOXF2, a member of the Fox protein family of transcription factors that regulate the expression of genes involved in embryogenic development as well as adult life. Our in vitro studies show that the half-life of mutant FOXF2 is reduced compared to that of wild type. Foxf2 is expressed in the cochlea of developing and adult mice. The mouse knockout of Foxf2 shows shortened and malformed cochleae, in addition to altered shape of hair cells with innervation and planar cell polarity defects. Expressions of Eya1 and Pax3, genes essential for cochlear development, are reduced in the cochleae of Foxf2 knockout mice. We conclude that FOXF2 plays a major role in cochlear development and its dysfunction leads to SNHL and developmental anomalies of the cochlea in humans and mice.